Fentanyl-induced transformations in composition of lipid droplets in central nervous system cells revealed by ramanomics - Rahul K. Das; Andrey N. Kuzmin; Artem Pliss; Supriya D. Mahajan; Shobha Shukla; Paras N. Prasad (Journal of Lipid Research, 2025)
Quantitative characterization of the transformations of subcellular molecular environment in response to fentanyl exposure in human microglia and astrocytes is warranted to provide insight into the regulation of neuroinflammatory responses and neural survival in the scenario of opiate drug addiction. Cytoplasmic lipid droplets (LD) act as depot for exogeneous hydrophobic molecules, such as fentanyl, which can lead to increased drug accumulation and alteration of their metabolism. In the present work, we have used an emerging Ramanomics technique that combines quantitative microlipid droplets -Raman spectrometry with biomolecular component analysis to unravel fentanyl induced changes in concentrations of phospholipids, sterols, glycogen, sphingomyelin, phosphocholine as well as RNA and proteins, in the LDs of microglia and astrocytes. The clinical relevance of these findings includes the potential to advance understanding of fentanyl's impact on the central nervous system at a molecular level. The observed alterations in lipid droplet composition, including changes in phospholipids, cholesterol esters, and glycogen accumulation, suggest that fentanyl overdose disrupts cellular homeostasis in microglia and astrocytes. This disruption could contribute to neuroinflammatory responses and impaired neural function, which are critical factors in opioid addiction and withdrawal. By utilizing Ramanomics as a noninvasive, real-time analytical tool, we can better assess fentanyl-induced cellular changes, paving the way for improved diagnostic assays and therapeutic strategies for opioid addiction and overdose treatment.